Modeling golf ball roll with a variable coefficient of friction - Burritt, A.; Henrikson, E. (Sports Engineering, 2024)
Work on modeling golf ball roll on a flat putting surface with both a constant and variable coefficient of rolling friction is presented, using the roll model derived by Penner. Experimental data using overhead cameras to capture the entirety of a putt`s roll on a number of surfaces is presented, as well as a method of fitting both constant and variable coefficients of friction from this data. Behavior of the variable coefficient of friction relative to golf ball velocity for the various surfaces is discussed in detail based on the experimental data analysis. It was found that the rolling friction coefficient decreased with decreasing velocity on three of the four surfaces studied, while the fourth demonstrated the opposite behavior, that is, greater rolling resistance as the golf ball slowed. Finally, putt roll out distance predictions from the two models with constant and variable coefficients of friction were compared to a separate set of experimental data, and conclusions were drawn for future model implementation and use.